Novel Pharmacologic Candidates for Treatment of Primary Open-Angle Glaucoma - Lu, Louise J. (Yale J Biol Med, 2017)
Primary open-angle glaucoma (OAG) affects approximately 45 million people worldwide and more than 2.5 million people aged 40 years or older in the United States. Pharmacologic treatment for glaucoma is directed towards lowering intraocular pressure (IOP) to slow disease progression and delay visual field loss. Current medical treatment options for the lowering of IOP include the following classes of topical medications: beta-adrenergic antagonists, alpha-adrenergic agonists, cholinergic agonists, carbonic anhydrase inhibitors, and prostaglandin analogs. Issues with existing drugs include failure to achieve target IOP with monotherapy, drug-related side effects, and low patient compliance with multiple daily administration of eye drops. In recent years, the scientific and medical community has seen encouraging development of novel classes of drugs for primary OAG, the majority of which lower IOP by targeting the trabecular meshwork outflow pathway to increase aqueous humor outflow. Among the most promising new pharmacologic candidates are rho kinase inhibitors including ripasudil (K-115), netarsudil (AR-13324), and AMA0076; adenosine receptor agonists including trabodenoson (INO-8875); and modified prostaglandin analogs including latanoprostene bunod (LBN, BOL-303259-X) and ONO-9054. This study aims to systematically review and summarize the most recent developments in clinical trials for new pharmacologic options for the treatment of primary open-angle glaucoma.